2019
DOI: 10.7150/jca.29327
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Inhibition of EGFR and HER2 via Afatinib Augments the Radiosensitivity of Nasopharyngeal Carcinoma Cells

Abstract: Ionizing radiation (IR) is the central component of the therapeutic scheme for nasopharyngeal carcinoma (NPC) at present. Previous studies show that inhibition of epidermal growth factor receptor (EGFR) enhances the radiosensitivity of NPC; however the effects of EGFR-targeted agents are limited. In this study, we observed that simultaneously inhibition of EGFR and HER2 by afatinib could augment the radiosensitivity of NPC cells; this approach has an advantage over erlotinib-mediated inhibition of EGFR alone. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Another group of EGFR inhibitors, tyrosine kinase inhibitors including gefitinib and erlotinib, failed to show promising results in patients with recurrent/metastatic NPC [41]. However, a new generation of EGFRi, AFA, which is an irreversible EGFR/HER2 inhibitor, was found to inhibit cell growth, augment the anticancer effect of gemcitabine [42], and enhance radiosensitivity in NPC [43]. In the current study, we showed that either ERB or AFA could inhibit NPC PDX tumor growth.…”
Section: Egfr Is a Target In Npc Managementmentioning
confidence: 53%
“…Another group of EGFR inhibitors, tyrosine kinase inhibitors including gefitinib and erlotinib, failed to show promising results in patients with recurrent/metastatic NPC [41]. However, a new generation of EGFRi, AFA, which is an irreversible EGFR/HER2 inhibitor, was found to inhibit cell growth, augment the anticancer effect of gemcitabine [42], and enhance radiosensitivity in NPC [43]. In the current study, we showed that either ERB or AFA could inhibit NPC PDX tumor growth.…”
Section: Egfr Is a Target In Npc Managementmentioning
confidence: 53%
“…Afatinib inhibits EGFR and ErbB-2 tyrosine kinase activity and suppresses NPC cell proliferation by arresting the cell cycle [ 108 ]. The combination of Afatinib and Gemcitabine (GEM) have shown significant anti-tumor efficacy in NPC xenograft models [ 108 , 109 ].…”
Section: The Role Of Egfr Targeting In Nasopharyngeal Carcinomamentioning
confidence: 99%
“…Afatinib inhibits EGFR and ErbB-2 tyrosine kinase activity and suppresses NPC cell proliferation by arresting the cell cycle [ 108 ]. The combination of Afatinib and Gemcitabine (GEM) have shown significant anti-tumor efficacy in NPC xenograft models [ 108 , 109 ]. In addition, Erlotinib and Afatinib could enhance the sensitivity of tumors to chemoradiotherapy by inhibiting DNA damage repair [ 105 , 108 ].…”
Section: The Role Of Egfr Targeting In Nasopharyngeal Carcinomamentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that AFT decreases the levels of phospho-EGFR and phospho-HER2 and remarkably inhibits cancer cell proliferation and survival. 27,28 Downregulation of EGFR or HER2 directly inhibits PI3K/Akt/mTOR signaling, triggering apoptosis. 29,30 In NPC, CDDP treatment (alone)…”
Section: Apoptotic Effects Of the Drug Combination On Hone1 Cellsmentioning
confidence: 99%